The Liber elegantiarvm: a Catalan-Latin dictionary at the crossroads of fifteenth-century European culture - Esteve, Joan (Lexica Latina Medii Aevi, 2012)
The 'Liber elegantiarum' (Venice 1489), by the Valencian notary Joan Esteve (fl. c. 1442-1487), is an outstanding and quiet original product of early humanistic European lexicography. Conceived partly as a bilingual Catalan-Latin dictionary, it by far surpasses this goal to become in addition an epistolary manual and an aid to grammar, besides providing an often picturesque collection of humanist sayings and literary excerpts. Above all it offers dramatic evidence of the multifacetted expansion of Italian humanism and the crucial role played by the brilliant Neapolitan court of the King of Aragon. As a Romance lexicon, Joan Esteve's work is also one of the first great repertories to include the vernacular as a source language (slightly after Tranchedini's 'Vocabolario') and probably the first to be printed, before Palencia's 'Universal Vocabulario' (1490), Nebrija's 'Dictionarium' (c. 1495) or Valla da Girgenti's 'Vocabularium vulgare' (1500)